Editorial - Apivatthakakul, MD, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery Volume 44 / Number 1-2 January-April 2020 is continue to published in this difficult period of the COVID-19 pandemic. The situation in Thailand is controllable with low death rate and very successful in term of health care system for all Thais. The Orthopaedic Surgeon has to postpone and delayed the elective case and prepare for COVID -19 control in every hospital. However, the academic activity of RCOST still moving forward, adapting the conference to online activity almost of them including the board examination of this year. This issue in your hand consists of several interesting articles with one case report and 5 original papers. In this issue include new technique of the surgery in sports, 2 interesting innovation in hip arthroplasty using the smartphone and innovative fixation for very low distal humerus fracture which difficult to manage or need arthroplasty. Our journal is making progress in a positive way with supporting from the RCOST committee and all RCOST members who submit their valuable work in Orthopaedic field to demonstrated the up to date knowledge and skill or basic knowledge of Administration system to improve national policy in treating Orthopaedic patients. We hope we will pass this pandemic in very near future and setup not only the new normal for life but also for the new normal treatment for our patient.